THE TALE OF KIEU AND LOVE SONGS IN VIETNAMESE FOLK SONGS - La Mai Thi Gia (Tạp chí Khoa học Đại học Đà Lạt)
From collected folk songs, we learn that “The Tale of Kieu” plays many important roles in “challenge and response” singing and love match songs. First, the plot is used as the main material in the songs. Second, the characters in “The Tale of Kieu” are often chosen by men and women in singing to briefly express their circumstances, personalities, moods, emotions, etc., in a way that is easy for all listeners to immediately understand. In this case, the characters of “The Tale of Kieu” are used as classical references in the songs. And third, which is also the most interesting aspect of the purpose of using “The Tale of Kieu” in response singing, the details, content, and characters in “The Tale of Kieu” are used for the two sides to test each other to see if the other person remembers, has memorized “The Tale of Kieu” or not, or knows how to use “The Tale of Kieu” in a flexible way.